Analisis Penerapan Etika Bisnis Islam pada Transaksi Penjualan Online di Shopee - Puji Lestari, Sumarti; Misbakhussurur (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
Online sales have become a phenomenon that dominates the global market, including on popular platforms such as Shopee. In this context, it is important to evaluate business practices ethically, especially for business people who follow the principles of Islamic Business Ethics. Sellers must be trustworthy by displaying an attitude of openness, honesty, optimal service, and doing good in everything, especially those related to community service. This research aims to analyze the application of Islamic Business Ethics in online sales transactions on the Shopee platform. The analysis results show that although there are efforts to implement Islamic Business Ethics, there are still challenges faced in the context of online transactions. This research provides a better understanding of how Islamic Business Ethics can be applied effectively in the online business environment, as well as providing recommendations for improving its implementation on platforms such as Shopee.